Molecular phylogeny and taxonomy reveal two new genera and five new species in Phanerochaetaceae (Polyporales) from Yunnan, Southwest China - Ying Xu; Yang Yang; Xin Yang; Daxiang Chen; Wen Zheng; Kaize Shen; Sicheng Zhang; Changlin Zhao (MycoKeys)
In the present study, two new genera Paradonkia, and Neodonkiella, and five new species, viz. Paradonkia farinacea, Neodonkiella yinjiangensis, Phanerochaete albocremea, Phanerochaete fissurata, and Phanerochaete punctata collected from southern China, are proposed based on a combination of morphological features and molecular evidence. Paradonkia farinacea is characterized by the resupinate, membranaceous basidiomata with pale cream to gray cream hymenial surface and a monomitic hyphal system with simple septa and clamp connections; Neodonkiella yinjiangensis is characterized by soft coriaceous basidiomata, a monomitic hyphal system and ellipsoid basidiospores (3.5–5 × 2–2.5 µm); Phanerochaete albocremea is characterized by resupinate basidiomata with white to a pale cream hymenial surface, and ellipsoid basidiospores (3.5–5 × 2–3 µm); Phanerochaete fissurata is characterized by gray-brown and cracked hymenial surface, and ellipsoid basidiospores (4–5.5 × 2–3 µm) and Phanerochaete punctata is characterized by farinaceous basidiomata, a monomitic hyphal system, and ellipsoid basidiospores. Sequences of the internal transcribed spacers (ITS) and the large subunit (nLSU) of the nuclear ribosomal DNA (rDNA) markers of the studied samples were generated. Phylogenetic analyses were performed using the maximum likelihood, maximum parsimony, and Bayesian inference methods. The phylogram based on the ITS+nLSU rDNA gene regions, revealed that two new genera, Paradonkia and Neodonkiella, belong to the family Phanerochaetaceae, and three new species belong to the genus Phanerochaete in the family Phanerochaetaceae.